Kreatifitas Pranata Laboratorium Pendidikan (PLP) di Laboratorium dalam Rangka Menunjang Tri Darma Perguruan Tinggi dengan Pembuatan Almari Pengering Sampel Beserta Hasil Ujinya - Sri Harjanto; Indra Gunawan; J Jufriyah (UPT Laboratorium Terpadu, Universitas Diponegoro, 2019)
PLP (Educational Laboratory Institution) is a position that has the scope of duties, responsibilities and authorities to carry out the management of an educational laboratory with the rights and obligations given in full by authorized officials. A PLP in Higher Education in carrying out their daily tasks in the laboratory is required to be creative and active in serving the activities of students or lecturers, both in the form of Practicum, Research or Community Service. From this observation, there are still many students lining up to use certain instrument facilities, so on this occasion we tried to be creative to make sample dryer cabinets with the aim of helping student activities in the laboratory especially in providing supporting facilities. With the method of measuring the accuracy of evaporation of water content in the sample. We hope that in the future it will all be done to meet the needs of students and complete facilities in the scope of the laboratory, even though it starts on a small scale or can be said to be a simple level. From the results of this creativity as a comparison Oven is used, with the test results having a fairly high level of accuracy, the range of differences between 0.10 - 0.9 gr .. With high creativity and discipline from a PLP in a College, it can be started from simple things such as in making a sample dryer cupboard, it is hoped that it will help facilitate students in their activities in the laboratory.